Prevalence and occupational exposure to zoonotic diseases in high-risk populations in the Free State Province, South Africa - van der Westhuizen, Cornelius G.; Burt, Felicity J.; van Heerden, Nina; van Zyl, Willie; Anthonissen, Tonia; Musoke, Jolly (Frontiers in Microbiology, 2023)
Introduction: Zoonotic diseases are responsible for 2.5 billion human cases globally and approximately 2.7 million deaths annually. Surveillance of animal handlers and livestock for zoonotic pathogens contributes to understanding the true disease burden and risk factors within a community. This study investigated the prevalence of selected zoonoses in cattle, farm workers and occupational exposure to endemic zoonotic diseases and their associated risk factors. Methods: Sputum samples from farmworkers were screened for Mycobacterium bovis (M. bovis). Blood specimens from farmworkers and archived sera were tested for serological evidence of Brucella sp., hantaviruses, and Leptospira sp. Communal and commercial cattle herds were tested for bovine tuberculosis and brucellosis. Results: M. bovis was not isolated from human samples. A total of 327 human sera were screened, and 35/327 (10.7%) were Brucella sp. IgG positive, 17/327 (5.2%) Leptospira sp. IgM positive, and 38/327 (11.6%) hantavirus IgG positive (95% CI). A higher proportion of Brucella sp. IgG-positive samples were detected among veterinarians (p-value = 0.0006). Additionally, two cattle from a commercial dairy farm were bovine tuberculosis (bTB) positive using the bTB skin test and confirmatory interferon-gamma assay. A higher percentage of confirmed brucellosis-positive animals were from communal herds (8.7%) compared to commercial herds (1.1%). Discussion: These findings highlight the brucellosis and M. bovis prevalence in commercial and communal herds, the zoonotic disease risk in commercial and subsistence farming in developing countries, and the occupational and rural exposure risk to zoonotic pathogens.